Bioprospecção de moléculas bioativas e antagonismo entre waitea circinata warcup & talbot e patógenos do arroz - Carvalho, Jacqueline Campos Borba de (2016)
Rice is one of the most important cereal in the world, but its productivity is affected by fungal diseases such as blast, brown spot, scald, sheath rot, sheath blight and stain of the sheath. Mycorrhizal fungi are capable of producing secondary metabolites that can be used to control pathogens. This study aimed to evaluate the potential of isolated mycorrhizal and their secondary metabolites in antagonism to the rice pathogens. The isolate mycorrhizal was characterized biochemically (cell wall and co - cultivation). We evaluated the mycorrhizal mycelia efficiency as well as their extracts and compounds in the inhibition of the mycelial growth, spore germination and formation of appressorium Magnaporthe oryzae. The efficiency of the pairing of volatile and non - volatile metabolites, and the efficiency of mycelium of Waitea circinata to other rice pathogens it was conducted in two trials. Four extracts of W. circinata (crude, mycelial, lyophilized and mycelial mass) were obtained and used in in vitro assays with pathogens. The tests for the suppression of leaf blast were also conducted in the greenhouse with the mycelium, extracts and mycorrhiza compounds. The completely randomized design was used for all tests. W. circinata produces Indolacetic Acid in vitro and showed enzymatic activity of glucanase, chitinase and protease when in cultivation with wall of the pathogens and co -cultivation. The mycorrhizal mycelia inhibited the mycelial growth of all rice pathogens in vitro. The isolated mycorrhizal was efficient in vitro production of volatile and non- volatile metabolites reducing mycelial growth of Sarocladium oryzae 94.41% and 53%, respectively. The mycelium of mycorrhiza to the concentration 10 g / L reduced the growth of M. oryzae by 97.92 % and has been effective and active even after autoclaving reducing the area of the colony by 93.53%, 77.30%, 31.07% and 4.42 % of Cochliobolus miyabeanus , Monographella albescens and Rhizoctonia oryzae - Ro93 and Ro88, respectively. In greenhouse the mycelium of mycorrhiza (10g/L En07 + M.o.) suppressed leaf blast at 83.89 %. Non- volatile metabolites of W. circinata inhibited in 48.95 % growth of M. oryzae. The analysis of spectrometric high resolution mass (HRMS) showed that the extract from the mycelial mass (MME), crude extract (CE) and lyophilized extract (LE) had the same chemical profile that can be attributed to sphinganine. The MME ( 700 / mL ) at 24 hours after installation of the test reduced the formation of appressorium of M. oryzae in 75.71 %, respectively. In the greenhouse, MME + M.o. suppressed the severity of leaf blast in 77.01 % and reduced AUDPC by 92.38 %. The results of this study indicate that the MME W. circinata is promising in biocontrol of the rice diseases.